Optimizing Student Learning Outcomes in Higher Education: The Efficacy of Learning Management Systems (LMS) - Imamuddin, M.; Isnaniah, Isnaniah; Hadini, Hadini; Dewi, Merry Prima; Charles, Charles (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Technological developments have impacted all sectors, including the education sector. This requires the education sector, especially the learning sector, to be innovative. Be innovative in implementing learning, one of them is using e-learning such as Learning Management Systems (LMS) and others. This research aims to determine the effectiveness of using LMS in the lectures of Teacher Professional Education (PPG) students. This research is experimental research, with a sample of PPG students. Data analysis using N-Gain and t-test. Based on the research results, it was found that student learning outcomes had increased. As many as 77.8% of students' learning outcomes were of medium criteria, and 22.2% were high. Based on the t-test results, using LMS media can effectively achieve learning outcomes in PPG student learning evaluations. This research for Islamic education management implies that it can be a reference for future researchers to study the use of LMS in distance learning in Islamic educational institutions more profoundly and comprehensively.